Simultaneous self-created transobturator tape and laparoscopic extraperitoneal vaginal support in patients with stress urinary incontinence and prolapse of the anterior and apical vaginal compartments. (September 2016) - Ignjatovic, Ivan; Basic, Dragoslav; Potic, Milan; Dinic, Ljubomir; Stankovic, Jablan; Pavlovic, Svetlana; Milic, Vladimir; Skakic, Aleksandar
Abstract: Objective: Stress urinary incontinence (SUI) is frequently associated with prolapse of the apical and anterior vaginal compartments. The standard treatment of SUI is transobturator tape (TOT). The usual treatment of prolapse (anterior colporrhaphy) has a high recurrence rate. The aim of this study is to evaluate the results of the treatment of SUI and concomitant anterior and apical prolapse with self-created transobturator tape and simultaneous laparoscopic anterior and apical support. Study design: A total of 36 patients with SUI and prolapse of the anterior and apical compartments were underwent operations. The mean follow-up was 18 months. Self-created transobturator tape and laparoscopical support of the anterior and apical compartment prolapse were performed in all patients. The most important symptoms of prolapse and incontinence, the anatomical outcome, and complications were evaluated before and after the surgery. Results: Treatment of incontinence and anterior and apical prolapse was successful in 33/36 (91.7%), 30/36 (83.3%) and 31/36 (86.1%) patients, respectively ( p < 0.0001). There is a significant reduction of vaginal bulging and pelvic pressure ( p < 0.0001). Frequency and urgency were significantly reduced ( p < 0.0007 and p < 0.03 respectively). There was no significant deterioration of the posterior compartment. The most important complications were bladder perforation in 2/36 (5.5%) patients and temporary urinary retention in 3/36 (8.3%) patients (Clavien-Dindo grade 3). Conclusion: Simultaneous laparoscopic anterior and lateral extraperitoneal support and transobturator tape are effective in the treatment of patients with both conditions.